Life Skills Education as a Strategy to Improve Clean and Healthy Living Behavior at SDN 039 Long Ikis: Edukasi Life Skills Sebagai Strategi Peningkatan Perilaku Hidup Bersih dan Sehat di SDN 039 Long Ikis - Nugraheni, Elisa Dwi; Mariyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Education plays a vital role in shaping qualified human resources, including in the health sector, by fostering essential life skills. One key area of focus is the cultivation of clean and healthy living behaviors from an early age, particularly among elementary school students. Health is a fundamental determinant of an individual’s quality of life and overall productivity. In East Kalimantan, the incidence of Acute Respiratory Infections (ARI) among toddlers remains significantly high at 22.7%, exceeding the national average. Simple preventive measures, such as handwashing with soap, have been proven effective in reducing the transmission of infectious diseases. The objective of this activity is to improve students' knowledge and practice of PHBS, particularly in preventing infectious diseases such as diarrhea and ISPA, with a focus on the habit of Handwashing with Soap. This activity was conducted on July 25, 2025, with the target program being all 24 students in grades I to VI of SDN 039 Long Ikis. The method used an interactive approach that includes material presentation, educational games, and group discussions. The results of the activity showed that all students participated actively and enthusiastically throughout the activity, both during the presentation and practice sessions. This program has succeeded in building students' awareness of the importance of clean and healthy living behaviors and getting them used to Handwashing with Soap as a disease prevention effort.